Upaya Meningkatkan Berpikir Kritis melalui Media Pembelajaran Diorama Tata Surya pada Siswa SD - Heri Irawan; Intan Maulidah; Syailin Nichla Choirin Attalina (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Critical thinking skills are a fundamental aspect that needs to be instilled early in the educational process in elementary schools. However, the application of conventional learning media such as textbooks and worksheets tends to be less supportive of the development of these skills, especially in complex materials such as the solar system. To overcome this, the use of solar system diorama media is considered capable of bridging students' conceptual understanding with more contextual visual and exploratory experiences. Through a constructivist approach, students are given space to be actively involved in observing, discussing, and linking materials to real phenomena, so that their critical thinking skills can be honed more optimally. This study aims to evaluate the effectiveness of the use of diorama media in improving the critical thinking skills of elementary school students and examine students' responses to this learning method. The results of this study are expected to contribute to the development of innovative learning strategies that can support the quality of elementary education.